Astaka Ghetaran Senada / Ainie Naziera Muhammad Yusof ... [et al.] - Muhammad Yusof, Ainie Naziera; Noorrahim, Nursyifaa’ Nabilah; Ismail, Sofea; Abdul Karim, Norashakin (2024)
Our assignment for this project was the Fusion Timber Challenge: Uniting Design and Sustainability. In essence, the main focus of this project is the use of timber as a retreat. In addition, we were instructed to integrate the design of the timber retreat with other elements such as materials, cultural practices, design styles, and innovative technology applications. In this project, we fused timber with traditional Malay materials and cultural elements. We have proposed with a brilliant idea to form from a subject matter, Gambus, which is known as traditionally a classical Malay music of Malay Ghazal and traditional performances such as Zapin and Hamdolok.